2021
DOI: 10.1002/pol.20210059
|View full text |Cite
|
Sign up to set email alerts
|

Parallel esterification of bio‐based dicarboxylic acids in small scale film reactors: A high‐throughput study

Abstract: The applicability of polyesters across a wide range of fields creates a demand for novel polyester structures that can offer advanced product performance. Two critical factors to the development of unique polymer architectures are the speed at which new polymeric systems can be synthesized and the available selection of monomers from which polymers are designed. Herein, we successfully demonstrate the applicability of a high‐throughput (HT) approach to polyesterification reaction between dicarboxylic acids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In a previous work we prepared new poly(PEG‐ co ‐fumarate)s and found that when low MW PEGs were used (200 and 400 Da), the precursors can be casted into hydrophilic films with elastomeric properties, by irradiation with UV light in presence of a suitable radical initiator (Irgacure 500), which were crosslinked by the formation of carbon–carbon bonds at the level of the fumaric acid monomers 27 . It is worth to mention that in this work the linear PEG‐fumarate prepolymers were obtained by simple melt polymerization reactions of PEG diol with fumaric acid, avoiding the use of metal catalyst, as was previously reported in the literature 28,29 . When these interesting materials were tested in drug delivery studies, we found that the release of hydrophilic doxorubicin was fast, presenting a pronounced burst phase.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a previous work we prepared new poly(PEG‐ co ‐fumarate)s and found that when low MW PEGs were used (200 and 400 Da), the precursors can be casted into hydrophilic films with elastomeric properties, by irradiation with UV light in presence of a suitable radical initiator (Irgacure 500), which were crosslinked by the formation of carbon–carbon bonds at the level of the fumaric acid monomers 27 . It is worth to mention that in this work the linear PEG‐fumarate prepolymers were obtained by simple melt polymerization reactions of PEG diol with fumaric acid, avoiding the use of metal catalyst, as was previously reported in the literature 28,29 . When these interesting materials were tested in drug delivery studies, we found that the release of hydrophilic doxorubicin was fast, presenting a pronounced burst phase.…”
Section: Introductionmentioning
confidence: 96%
“…27 It is worth to mention that in this work the linear PEG-fumarate prepolymers were obtained by simple melt polymerization reactions of PEG diol with fumaric acid, avoiding the use of metal catalyst, as was previously reported in the literature. 28,29 When these interesting materials were tested in drug delivery studies, we found that the release of hydrophilic doxorubicin was fast, presenting a pronounced burst phase. On the other hand, Paclitaxel, a hydrophobic drug, presented much slower and sustained release profiles.…”
Section: Introductionmentioning
confidence: 99%